KERANGKA TEORETIS KETERAMPILAN MENDENGARKAN AKTIF DI ERA DIGITAL: MODEL INTEGRATIF UNTUK INTERVENSI SISWA SMA - Rika Rahayu; Uman Suherman; Ibrahim Al-Hakim (FOKUS : Kajian Bimbingan dan Konseling dalam Pendidikan, 2026)
The digital era has transformed the communication landscape of Indonesian adolescents. The phenomena of phubbing and technoference have become serious barriers to the development of active listening skills (ALS). Data from APJII (2024) shows thatinternet penetration among adolescents reaches 87.02% with usage duration of 6-10 hours per day. This article develops a "Digital-Real Bridge" Theoretical Framework through an integrative review of 50 reputable sources. The framework conceptualizes ALS through three dimensions (cognitive, affective, and behavioral) while accounting for digital era barriers. The framework identifiesspecific mechanisms by which digital technology disrupts each dimension of ALS and proposes targeted intervention strategies rootedin Social and Emotional Learning (SEL) and Social Skills Training (SST) principles. Key contributions include: (1) theoretical integration of previously separate constructs, (2) operationalization of a 10-session modular program, and (3) culturally-responsive adaptation principles for implementation within the guidance and counseling context in Indonesia. This study employs an integrative literature review design using the Torraco (2005) and Whittemore and Knafl (2005) frameworks, synthesizing 50 reputable sources across developmental psychology, communication, educational technology, and guidance and counseling disciplines.